Catherine Watson interviewed by Paula Hamilton in the NSW Bicentennial oral history collection - Watson, Catherine, 1904-; Hamilton, Paula; N.S.W. Council on the Ageing; Oral History Association of Australia. N.S.W. Branch; NSW Bicentennial Oral History Project (1987)
Born at Helensburg, NSW, Watson speaks of her parents' background; family; home; memories of childhood; family roles; fathers work in colliery; recreation; chores at home; family life; 1917 strike; food and diet; the mining community; school; finding work; domestic service in Sydney and Wollongong, families she worked for, work routines, conditions, different jobs, looking after children, living conditions; recreation; social life; her sisters' careers; meeting husband; marriage; her husband; the Depression.
Includes index.
Recorded by the NSW Bicentennial Oral History Project, funded by a bicentennial grant to the NSW Council on the Ageing and the Oral History Association of Australia (NSW).
Also available online
Timed summary and transcript available.
Keywords: Watson, Catherine, -- 1904- -- Interviews; Women household employees -- New South Wales -- Social conditions -- 1901-1945.; Women household employees -- Employment -- New South Wales